Why Too Soon? Early Initiation of Sexual Intercourse Among Adolescent Females in Ethiopia: Evidence from 2016 Ethiopian Demographic and Health Survey - Turi E; Merga BT; Fekadu G; Abajobir AA (International Journal of Women's Health, 2020)
Ebisa Turi,1 Bedasa Taye Merga,2 Ginenus Fekadu,3 Amanuel Alemu Abajobir4 1Department of Public Health, Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 2School of Public Health, College of Health and Medical Sciences, Haromaya University, Harar, Ethiopia; 3Clinical Pharmacy Unit, Department of Pharmacy, Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 4Maternal and Child Wellbeing Unit, African Population and Health Research Centre, Nairobi, KenyaCorrespondence: Ginenus FekaduClinical Pharmacy Unit, Department of Pharmacy, Institute of Health Sciences, Wollega University, Nekemte, Oromia, EthiopiaTel +251 917137145Fax +251 57 6617980Email take828pharm@gmail.comBackground: Early sexual initiation – sexual activity that begun earlier than 18 years of age – is among risky sexual behaviors which may be associated with increased risks of adverse outcomes such as sexually transmitted infections (STIs), unwanted pregnancy and unsafe abortions. However, there is no nationally representative evidence on early initiation of sexual intercourse and its determinant factors among adolescent females in Ethiopia.Methods: Data were extracted from the  2016 Ethiopian Demographic and Health Survey (EDHS) to assess early initiation of sexual intercourse and factors contributing to it in adolescent females. The analysis included a weighted sample of 3881 adolescent females aged 15– 19 years. A multivariable logistic regression analysis was conducted and the results were presented as adjusted odds ratio (AOR) at 95% confidence interval (CI), declaring statistical significance at a p-value < 0.05 in all analyses.Results: About 1 in 5 (21.9%, 95% CI: 20.5%, 23.33%) adolescent females experienced early sexual debut. Administrative regions (Amhara, AOR = 2.3, 95% CI: 1.30, 4.09 and Gambella, AOR = 4.89, CI 95%: 1.08, 22.07), religion (Muslim, AOR = 1.76, 95% CI: 1.24, 2.49), substance use (e.g., ever chewed khat, AOR = 2.02, 95% CI: 1.47, 2.77, ever drunk alcohol, AOR = 1.83, 95% CI: 1.35, 2.48) and having no knowledge on family planning (AOR = 4.47, 95% CI: 2.22, 8.99) were found to have statistically significant association with early sexual debut in adolescent females. Whereas any levels of formal education decreased the odds of early sexual debut (primary, AOR = 0.44, 95% CI: 0.35, 0.56; secondary, AOR = 0.19, 95% CI: 0.13, 0.28, and higher, AOR= 0.31, 95% CI: 0.15, 0.63). Similarly, all categories of wealth indices as compared to the poorest were protective of early sexual initiation in adolescent females (AOR = 0.40– 0.57) as was for education as compared to no education (AOR = 0.19– 0.44).Conclusion: A significant proportion of adolescent females initiate early sexual intercourse in Ethiopia and multifaceted factors appear to determine their early sexual experiences. Contextualized interventions including strengthening information, education and communication on adverse consequences of early sexual initiation in regions and improving contraceptive knowledge of teenagers will play a paramount role.Keywords: early initiation of sexual intercourse, female adolescents, EDHS, Ethiopia